Professional LAMP : Linux, Apache, MySQL, and PHP Web development - Naramore Elizabeth (Wiley Pub. Inc, 2006)
* The combination of Linux, Apache, MySQL, and PHP is popular because of interaction, flexibility, customization, and-most importantly-the cost effectiveness of its components